A comparative study of mechanisms of the adsorption of CO2 confined within graphene–MoS2 nanosheets: a DFT trend study - Enujekwu, Francis M.; Ezeh, Collins I.; George, Michael W.; Xu, Mengxia; Do, Hainam; Zhang, Yue; Zhao, Haitao; Wu, Tao (Royal Society of Chemistry, 2019)
The space within the interlayer of 2-dimensional (2D) nanosheets provides new and intriguing confined environments for molecular interactions. However, atomic level understanding of the adsorption mechanism of CO2 confined within the interlayer of 2D nanosheets is still limited. Herein, we present a comparative study of the adsorption mechanisms of CO2 confined within graphene–molybdenum disulfide (MoS2) nanosheets using density functional theory (DFT). A comprehensive analysis of CO2 adsorption energies (EAE) at various interlayer spacings of different multilayer structures comprising graphene/graphene (GrapheneB) and MoS2/MoS2 (MoS2B) bilayers as well as graphene/MoS2 (GMoS2) and MoS2/graphene (MoS2G) hybrids is performed to obtain the most stable adsorption configurations. It was found that 7.5 Å and 8.5 Å interlayer spacings are the most stable conformations for CO2 adsorption on the bilayer and hybrid structures, respectively. Adsorption energies of the multilayer structures decreased in the following trend: MoS2B > GrapheneB > MoS2G > GMoS2. By incorporating van der Waals (vdW) interactions between the CO2 molecule and the surfaces, we find that CO2 binds more strongly on these multilayer structures. Furthermore, there is a slight discrepancy in the binding energies of CO2 adsorption on the heterostructures (GMoS2, MoS2G) due to the modality of the atom arrangement (C–Mo–S–O and Mo–S–O–C) in both structures, indicating that conformational anisotropy determines to a certain degree its CO2 adsorption energy. Meanwhile, Bader charge analysis shows that the interaction between CO2 and these surfaces causes charge transfer and redistributions. By contrast, the density of states (DOS) plots show that CO2 physisorption does not have a substantial effect on the electronic properties of graphene and MoS2. In summary, the results obtained in this study could serve as useful guidance in the preparation of graphene–MoS2 nanosheets for the improved adsorption efficiency of CO2.